HOMESIDE: home-based family caregiver-delivered music and reading interventions for people living with dementia: protocol of a randomised controlled trial - Sabine Braat; Felicity Anne Baker; Imogen Clark; Young-Eun Claire Lee; Thomas Wosch; Helen Odell-Miller; Nicola Lautenschlager; Jodie Bloska; Anna Bukowska; Ming H Hsu; Tone Kvamme; Agnieszka Smrokowska-Reichmann; et al. (BMJ Open)
Introduction Pharmacological interventions to address behavioural and psychological symptoms of dementia (BPSD) can have undesirable side effects, therefore non-pharmacological approaches to managing symptoms may be preferable. Past studies show that music therapy can reduce BPSD, and other studies have explored how formal caregivers use music in their caring roles. However, no randomised study has examined the effects on BPSD of music interventions delivered by informal caregivers (CGs) in the home setting. Our project aims to address the need for improved informal care by training cohabiting family CGs to implement music interventions that target BPSD, and the quality of life (QoL) and well-being of people with dementia (PwD) and CGs.Methods and analysis A large international three-arm parallel-group randomised controlled trial will recruit a sample of 495 dyads from Australia, Germany, UK, Poland and Norway. Dyads will be randomised equally to standard care (SC), a home-based music programme plus SC, or a home-based reading programme plus SC for 12 weeks. The primary outcome is BPSD of PwD (measured using the Neuropsychiatric Inventory-Questionnaire). Secondary outcomes will examine relationship quality between CG and PwD, depression, resilience, competence, QoL for CG and QoL for PwD. Outcomes will be collected at baseline, at the end of the 12-week intervention and at 6 months post randomisation. Resource Utilisation in Dementia will be used to collect economic data across the life of the intervention and at 6-month follow-up. We hypothesise that the music programme plus SC will generate better results than SC alone (primary comparison) and the reading programme plus SC (secondary comparison).Ethics and dissemination Ethical approval has been obtained for all countries. Results will be presented at national and international conferences and published in scientific journals and disseminated to consumer and caregiver representatives and the community.Trial registration numbers ACTRN12618001799246p; NCT03907748